VD_FINDINFO Jug / 2012 / 215 vom 10. August 2012 - VD Tribunal cantonal (2012)
CONTRAT D'ARCHITECTE, DILIGENCE, DÉFAUT DE LA CHOSE, HONORAIRES, MOEURS, REGISTRE DES POURSUITES | 373 al. 1 CO, 394 al. 3 CO, 397 CO, 398 al. 2 CO, 8a LP, 85a LP